Penerapan Cophenetic Correlation pada Pemilihan Metode Pembentukan Dendrogram untuk Mengelompokkan Alat Kontrasepsi Peserta KB Aktif dengan Pendekatan Bottom-Up: Studi pada Level Kabupaten/Kota di Provinsi NTT Tahun 2023 - Syfriza Davies Raihannabil (Badan Pusat Statistik Provinsi NTT, 2024)
NTT is a province with relatively high population growth and birth rates. High population growth and birth rates can hinder development. Therefore, the government initiated a program to reduce the birth rate and control the population growth rate through the family planning program (FPP). However, there are still many couples of childbearing age (PUS) in NTT who have not experienced the benefits and access to FPP. Therefore, this research aims to group districts/cities in NTT based on the contraceptive devices of active family planning participants. This research applies a bottom-up approach with the cophenetic correlation coefficient as the basis for selecting the dendrogram formation method. From the research results, the average linkage method with a cophenetic correlation coefficient of 0.884 is the best method for producing dendrograms. The research produced 4 optimal clusters: 1 district/city joined in cluster 1, 3 districts/cities joined in cluster 2, 2 districts/cities joined in cluster 3, and 16 districts/cities joined in cluster 4. Cluster 4 has the characteristics of using all tools contraception is low, even so low that it is categorized as a priority area for government intervention in FPP.